MELACAK RELASI HOAX DAN KEKUASAAN DI INDONESIA : STUDI KASUS PILKADA DKI TAHUN 2017 - ilmar, anwar; ode, samsul (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2019)
This study discusses post-truth politics in Indonesia by raising the case of hoaxes in the Election of Regional Head and Deputy Regional Head of DKI Jakarta in 2017. The study is motivated by a decline in the performance of democracy in Indonesia due to poor electoral and pluralism processes in Indonesia, based on data released by the Economist Intelligence Unit in 2017. In this case, the 2017 DKI Jakarta Election was considered to have contributed to the negative trend, mainly because its electoral process was filled with discourse hoaxes, or hoaxes related to politics and ERRI (ethnicity, religion, race and intergroup) Therefore, the aim of this study is to find out the root causes of the hoax phenomenon, and to examine its influence on the political configuration formed in the DKI Jakarta Regional Head Election in 2017. This study uses a hegemonic approach with discourse analysis that will dismantle the reality behind the hoax phenomenon in the 2017 DKI Jakarta Election. This study found that the elite's role is crucial as the cause of the rise of hoaxes in the 2017 DKI Jakarta Election. This research also found the existence of antagonism and political frontier between the pro and anti against Basuki Tjahaya Purnama or Ahok, one of the contestants of the Pilkada, due to massive hoax discourse related to politics and SARA thus forming a chain of equivalence diametric. This study concludes that the influence of elite hegemony is very strong against the emergence of post-truth politics in Indonesia.